Systems analysis in forecasting of interrelated random processes - Щелкалін, Віталій Миколайович (Technology audit and production reserves, 2013)
The paper draws attention to the need for applying systems analysis in the prediction of interrelated random processes, the need for focusing on the creation of systems methodologies in the prediction problems. For studying and analyzing the problem of structural identification in creating mathematical models of prediction there is a need to involve the experts with various fundamental knowledge and practical experience in the implementation of projects in their respective areas. In researches on the problems of structural identification of mathematical models of prediction, special attention should be paid to the human factor. Owing to the development of computers and modeling techniques, among which various decomposition methods and models get a widespread use, the systems studies of the problem of structural identification of predictive models are needed for the prediction of interrelated random processes.